Optimization of the Datu Soban Application as Part of Public Services in South Kalimantan Province of Social Services - Alfonsa Agustina Eka Cahyani; Mochamad Federico Azis; Agus Gusnadi; Ainaya Alfatihah; Mujahidin (Institute of Computer Science (IOCS), 2022)
This study examines how the development model of the data soban application is used to provide public services to the people of South Kalimantan for the welfare of the community. Descriptive research is research used by researchers in this study. Researchers describe facts, data, and information obtained from literature studies such as books, journals, and research results related to the research topic. In this study, it is explained that along with the development of technology and information, people's demands for the availability of fast, accurate, and factual information are increasing. This is also felt by the South Kalimantan Social Service as part of the local government tasked with improving the welfare of the community through various programs, one of which is distributing social assistance funds to people in need. South Kalimantan Province has 26 PPKS and 12 PSKS must be recorded accurately and factually. The goal is that the funds that are channeled are right on target. Therefore, the Social Affairs Office of South Kalimantan in collaboration with Kominfo developed an application model named Datu Soban which is used to facilitate public services and overcome the above problems to improve the welfare of the people of South Kalimantan.